Antimicrobial susceptibility of invasive and lower respiratory tract isolates of Streptococcus pneumoniae, 1998 to 2007 - Vanderkooi, Otto G (Pulsus Group Inc, 2009)
Previous surveys of antimicrobial resistance in Streptococcus pneumoniae have found differences depending on source of isolate (eg, higher resistance in lower respiratory tract [LRT] versus invasive isolate) and age (higher resistance in children versus adults). Susceptibility profiles in the Calgary Health Region (approximately 1.25 million population) over a 10-year period were studied. Prospective laboratory-based population surveillance for S pneumoniae disease has been conducted since 1998. Patient demographics and susceptibility testing were analyzed. In total, 2382 patient isolates were available for analysis from 1998 to 2007. Of these, 1170 isolates were invasive while 496 were LRT. Patient age distribution was: younger than five years, 14%; five to 17 years, 6%; 18 to 64 years, 56%; and 65 years or older, 24%. Mean patient age was 44.8 years and 60.0% were male. The overall incidence of nonsusceptibility was: penicillin, 8.2%; amoxicillin, 0.3%; cefuroxime, 6.2%; ceftriaxone, 1.7%; erythromycin, 8.8%; trimethoprim-sulfamethoxazole (TMP-SMX), 25.6%; clindamycin, 2.3%; and levofloxacin, 0.2%. Overall resistance rates were stable, except for increasing erythromycin resistance from 5.4% (1998) to a high of 14.2% (2004) (P=0.007). Isolates that were nonsusceptible to penicillin or TMP-SMX were more likely to be multidrug resistant (P<0.001) compared with penicillin- or TMP-SMX-susceptible isolates. Compared with invasive isolates, LRT isolates showed more resistance to penicillin, TMP-SMX, cefuroxime and erythromycin, and were more likely to be multidrug resistant. Isolates from children younger than five years of age are more likely to be multidrug resistant and resistant to erythromycin and cefotaxime. Ongoing surveillance of S pneumoniae isolates is important because resistance rates vary by source and patient age among health care regions.